2011
DOI: 10.4049/jimmunol.1100934
|View full text |Cite
|
Sign up to set email alerts
|

IL-21–Dependent B Cell Death Driven by Prostaglandin E2, a Product Secreted from Follicular Dendritic Cells

Abstract: In germinal centers (GCs), B cells are selected through interaction with follicular dendritic cells bearing immune complexes and follicular helper T (Tfh) cells secreting Tfh cytokines, including IL-21. To analyze these cellular interactions, we have explored culture conditions that can simulate GC B cell selection in vitro using a mouse follicular dendritic cell line, FL-YB. FL-YB cells efficiently enhanced viability of cocultured mouse B cells in a BAFF-dependent fashion. Interestingly, we found that additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…In the present study, we showed that activation of β 1 -AR in rat atria by anti-β 1 -AR IgG increased PGE 2 generation. The increase in PGE 2 generationmediated atria apoptosis is similar to that occurring in other tissues and was preceded by iNOS activation with an increase of NO [46][47][48]. The participation of PGE 2 in rat atria apoptosis shows that this cytokine is a modulator of the periodontal β 1 autoantibody stimulation/caspase effect.…”
Section: Discussionsupporting
confidence: 49%
“…In the present study, we showed that activation of β 1 -AR in rat atria by anti-β 1 -AR IgG increased PGE 2 generation. The increase in PGE 2 generationmediated atria apoptosis is similar to that occurring in other tissues and was preceded by iNOS activation with an increase of NO [46][47][48]. The participation of PGE 2 in rat atria apoptosis shows that this cytokine is a modulator of the periodontal β 1 autoantibody stimulation/caspase effect.…”
Section: Discussionsupporting
confidence: 49%
“…We established an in vitro culture system that generates BCL6 int RelB + IRF4 + GC precursors prior to BCL6 hi RelB − IRF4 − GC B cells, recapitulating the in vivo observations. As illustrated in Figure 8A, freshly isolated primary B cells were pulse-stimulated with anti-IgM to mimic in vivo antigen recognition, followed by seeding onto BAFF-expressing FL-YB cells for survival support (Magari et al, 2011). At day 3 of culture, T cell associated stimuli (αCD40 and IL-4/21) were washed away and cells were re-cultured in medium only for an additional half-day before analysis.…”
Section: Resultsmentioning
confidence: 99%
“…FL-YB expresses comparable levels of B cell activating factor (BAFF) to that of FDCs. It was kindly provided by Dr. Masaki Magari and cultured as described in a previous study (Magari et al, 2011). FL-YB cells were tested to be mycoplasma free and validated to be over-expressing BAFF that supports murine primary B cell survival.…”
Section: Methodsmentioning
confidence: 99%
“…The growth suppressive effect of PGE 2 is mediated via binding EP4, a PGE 2 R and candidate tumor suppressor [37]. CD40-activated B cells resist PGE 2 and have been suggested to serve as APCs for tumor vaccination within the suppressive TME [38–40]. Regardless of the form of B cell stimulation, regulatory mechanisms, mediated by macrophages and dendritic cells, are initiated upon activation (41,42).…”
Section: Discussionmentioning
confidence: 99%